Behavioural Information Processing - Penland, Patrick R. (Journal of Information and Knowledge, 1977)
The learning habits and patterns of people, the environmental cues that produces the stimulus, and the episodic occurrences for motivation of learning are discussed. Several episode linking motivations and objectives are mentioned. Learning projects are grouped into categories according to the source which directs them-such as self-learning, non-human resources, human resources, group resources and hybrid resources. The intrapersonal behaviour in the communication of information needs and the satisfaction of the same, the various aspects of the librarian patron interface as a learning process, the sequential behaviour as a mode for self-designed independent learning, are discussed. In conclusion, the influence of the environment on a learning project and the basic causes for starting and terminating of a learning project are highlighted.